Makna Moralitas Pada Film Nanti Kita Cerita Hari Ini - Tania, Najma Ayu; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia; Cahyani, Dewi Yuri (E-Jurnal Medium, 2024)
Film is a mass communication medium that is audio-visual in nature and has the aim of conveying certain social and moral message to its audience. The ability of films to infulence audiences is widely used by filmmakers to provide moral message in their films. One of the films that conveys the moral content in it a film entitled “ Nanti Kita Cerita Tentang Hari Ini “. This paper explains in the meaning of morality in films using Roland Barthes’ semantic method. This method focuses on the idea of two levels in signification ( two order of signification ), namely denotation and connotation in the film. The meaning of morality in the film is attached to an urban family, which includes: responsibility, autonomous morality, justice, and mutual forgiveness   Kata kunci: Film, Nanti Kita Cerita Tentang Hari Ini, Moral, Sem iotics .